Pengaruh Partisipasi Anggota terhadap Keberhasilan Koperasi (Suatu Kasus di Koperasi Produsen Sinar Jagung Priangan, Kecamatan Nagreg, Kabupaten Bandung) - Fathoni, Ilham Dwi; Karyani, Tuti; Qanti, Sara Ratna (Universitas Galuh, 2025)
The success of cooperative is the primary goal of every cooperative business entity. One factor that influences this is the active participation of members in the cooperative. The lack of member participation often becomes an issue, even though the success of cooperative greatly depends on the extent of member participation in supporting the activities and operations of the cooperative. This research aims to determine the level of success of the cooperative and the extent to which member participation influences the success uses a survey method involving 73 cooperative members selected using the proportionate stratified random sampling technique. The data analysis technique used is multiple linear regression analysis. The results show that the level of member participation falls within the high criteria with a percentage of 78,95%, and the success level of the KSJP cooperative is in the good category with percentage of 79,15%. The independent variables consist of member meetings, capital contributions, cooperative supervision, and service utilization cooperative, while the dependent variable is the success of the cooperative. The research results indicate that the success of the cooperative can be explained by the variables of member participation in meetings, member participation in capital contributions, member participation in supervision and cooperative services by 56,5%, while 43,5% is explained by other variables not examined in this study. Simultaneously, the variables of member meetings, capital contributions, cooperative supervisions, and service utilization significantly affect the success of KSJP, while partially, only service utilization significantly affects the success of the cooperative.